Academic Stress and Suicidal Ideation among Pakistani College Students: Mediating Role of Perceived Stress and Moderating Effects of Resilience and Impulsivity - Nazia Asmat*; Muhammad Avais; Saira Tariq; Anam Waheed; Afifa (`, 2025)
Academic stress has emerged as a major psychological concern among the Pakistani youth and has increasingly been linked to the development of the suicidal thoughts and tendencies. Guided by Integrated Motivational Volitional (IMV) model of suicidal behavior and Transactional Stress Theory this study explored how the academic stress contributes to suicidal ideation through perceived stress as a mediator and resilience and impulsivity as moderators. A cross sectional quantitative research design was applied with the total of 250 male college students between the ages of 17 to 21 years with a mean age of 19.0 and standard deviation of 1.2. The participants were selected from the private colleges situated in Lahore and Gujranwala in Pakistan. All participants completed the standardized psychological measures including the Educational Stress Scale for Adolescents (ESSA) the Perceived Stress Scale (PSS 10) the Connor Davidson Resilience Scale (CD RISC 10) the Barratt Impulsiveness Scale Short Form (BIS 11 SF) and the Suicidal Ideation Attributes Scale (SIDAS). Data analysis using PROCESS Macro Model 59 indicated that perceived stress significantly mediated the association between academic stress and suicidal ideation with an indirect effect of 0.22 and a significance level of p less than 0.001. Resilience was found to reduce the impact of perceived stress on the suicidal ideation with beta equal to minus 0.16 and p equal to 0.004 whereas impulsivity increased this association with beta equal to 0.18 and p equal to 0.001. The overall model accounted for 51 percent of the variance in suicidal ideation with R square equal to 0.51 that representing a large effect size. These findings identify perceived stress as a key psychological pathway connecting academic stress to suicidal ideation and underline the vital role of resilience development in educational and counseling environments. Keywords: Academic Stress, Perceived Stress, Suicidal Ideation, Resilience, Impulsivity, Pakistani Students